Statistical Evaluation of the Heavy Metals in the Sediments of Warri River and Environs - Imeokparia, E.G.; Jire, P. N. (European Journal of Applied Sciences, 2018)
This study was carried out to assess and characterize the pollution/contamination status of the sediments in Warri River and its environs in view of the increasing level of oil spillages induced by willful acts of vandalization, lack of maintenance of pipelines, aging facilities, accident, illegal bunkering, petroleum refinery and production, urbanization, industrial activities and indiscriminate dumping of wastes. A total of thirty-two sediments samples were collected from eight sampling stations, grouped into locations B1-B8 respectively and analyzed for heavy metals. The chemical data set generated were subjected to principal component analysis (PCA)/factor analysis (FA) and Hierarchical cluster analysis (HCA) to determine the subtle factors responsible for their distribution. The heavy metal concentrations of locations B1-B8 were further evaluated using enrichment factor (EF), Contamination factor (CF) and Pollution load index (PLI) to assess the level of pollution in the area. The Factor Analysis results revealed four sources of pollutants which are explained by four factors (1)petroleum production, oil spills and illegal bunkering/pipe line vandalization (2) iron/steel industries (3)vehicular emission(4) indiscriminate dumping of waste. The R and Q mode cluster analysis yielded three clusters respectively. The Contamination Factor (CF)showed that the sediments have considerable level of Cr contamination at locations B2, B3,B4 and B6 while Fe, Zn, Ni, V, Pb, Cd, Mn and Cu exhibited moderate contamination at locations B1-B7.The Pollution Load Index (PLI)revealed that locations B1-B6 shown progressive site deterioration with respect to the nine measured heavy metals. The Enrichment Factor (EF) indicated that Cr was moderately enriched at locations B1, B2, B4 and B6 while Zn, Ni, Cu, Cd, Mn, Fe, V, and Pb in the sediments ranged from background concentration to minimal enrichment. Since these heavy metals can become a threat to vegetation and animals and ultimately to humans through the food chain, it is important to continuously monitor the level of pollutants in the environment.